2005
DOI: 10.1021/ja053482t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assembly of Superquenchers in Signaling Molecular Interactions

Abstract: We have designed a novel molecular assembly of quencher molecules to form Superquenchers with excellent quenching efficiency. The Superquencher can be engineered as desired by assembling different types and different numbers of quencher molecules. By labeling a Superquencher to a molecular beacon, a 320 folds enhancement of fluorescent signal was achieved, compared to about 14-fold from a molecular beacon prepared with the same monomer quencher. Our molecular assembly approach can effectively improve the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
95
0
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 18 publications
2
95
0
5
Order By: Relevance
“…For the quencher role, superquenchers and metal nanoparticles have been tested. [9][10][11] In addition to improving photophysical properties, using nanomaterials as MB components offers several other advantages. First, such MBs might be easily separated, allowing for operations unique to heterogeneous assays such as washing and signal amplification.…”
Section: Introductionmentioning
confidence: 99%
“…For the quencher role, superquenchers and metal nanoparticles have been tested. [9][10][11] In addition to improving photophysical properties, using nanomaterials as MB components offers several other advantages. First, such MBs might be easily separated, allowing for operations unique to heterogeneous assays such as washing and signal amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the modular assembly [5] facilitates the additional incorporation of functionalities that can be easily introduced via the sfO. In an example of this concept, we prepared "superquenched" [6] tMBs by appending additional quencher moieties to the sfO.…”
mentioning
confidence: 99%
“…As an example, we constructed "superquenched" [6] tMBs by attaching additional Dabcyl quencher moieties to sfO 7 a (7 a* and 7 a**, Figure 4 A). The aim was to increase the fluorescence enhancement upon target addition by reducing the fluorescence of the closed tMB.…”
mentioning
confidence: 99%
“…8,9,13 Subsequent experiments showed that efficient quenching is not specific to oligomers of pyrene, and can be observed with other π-stacking fluorophores. Sequences containing benzopyrene and perylene in addition to pyrene (6,7) demonstrated fluorescent excited-state complexes (exciplexes) that were also highly sensitive to quenching by MV (Table 1). Significantly, in cases where both monomer and exciplex emission was present, the delocalized exciplex emission was much more efficiently quenched.…”
mentioning
confidence: 99%